The curriculum of Islamic education: theoretical and practical challenges - Ramdane, Tahraoui (Institut Terjemahan & Buku Malaysia Berhad, 2016)
Curriculum is hardly new. It has been associated with schooling and education since the antiquity. The dominant notion that reflects the goals of curriculum from its Islamic perspective is to embody and achieve two main chief characters of Islamic education; servitude and vicegerency of Allah on earth. However, in a contemporary world that is complicated, polarised, and increasingly dominated by western educational world view, the issues and challenges that the curriculum of Islamic education is facing became more critical, therefore, require deeper reflection and concern. Thus, this book provides a platform for those who are about to or are embarking on studies curriculum from the Islamic perspective. The readers will find thought provoking issues and ideas that are presented in a simple and easy to understand concept.